Предмет: Алгебра, автор: SabiB

сделайте пожалуйста 215 3)

Приложения:

Ответы

Автор ответа: Artem112
0
a^2-b^2=(a-b)(a+b)
\
( frac{1}{3}  sqrt{5} +3 sqrt{2} )^2-( 3 sqrt{2}-frac{1}{3}  sqrt{5}  )^2=
\
=( frac{1}{3}  sqrt{5} +3 sqrt{2} -3 sqrt{2}+frac{1}{3}  sqrt{5}  )( frac{1}{3}  sqrt{5} +3 sqrt{2} +3 sqrt{2}-frac{1}{3}  sqrt{5}  )=
\
=frac{2}{3}  sqrt{5} cdot 6 sqrt{2} = frac{2cdot6}{3}  sqrt{5cdot2} =4 sqrt{10}
Похожие вопросы
Предмет: Математика, автор: 2nz74pb2ih
Предмет: Қазақ тiлi, автор: Аноним